Third Conference on Nuclear Reactor Inspection (ICE, 2011)
Proceedings of the Conference on Nuclear Reactor Inspection, held 1-2 October 1984.
Conference proceedings.
Keywords: Nuclear reactors -- Inspection -- Congresses.; elektronické knihy; electronic books